Sustainable branding in luxury business development: The case of the Luxury Hospitality sector - Borralho, Inês (My University, 2023)
For many years, luxury was seen as never changing and almost untouchable industry when it comes to market adaptation since its consumers would search for these brands regardless of trends. Nonetheless, in a constantly evolving business scenario, all brands must adapt, not only in order to remain competitive but, in the specificity of the luxury scenario, also to have an adequate offer for the new generations and their inherent concerns. One of these concerns that the younger generation generally has is regarding sustainability and the protection of the resources that exist in the planet. Not only that but also the increasing awareness about social issues that are behind most of the big corporations. Therefore, there is a gap in understanding the applicability of sustainability in luxury companies when new business is being developed. Hence, this thesis aims to answer the question of “How do luxury companies implement sus-tainable branding within business development considering the enablers, drivers, barriers and challenges inherent to the branding process and its steps?”. Additionally, the author proposes to achieve the objectives of defining branding, luxury, sustainability, sustainable luxury branding and their inherent dimensions; identifying the phases of the sustainable branding process when inserted in a business development scenario; understanding what the drivers, enablers, challenges, and barriers in the sustainable branding process are; and exploring the sustainable branding process in a luxury company within the hospitality sector. When it comes to the key concepts of this thesis, they definitely are branding, luxury, sustainability, and sustainable luxury branding. The first three are key to understand the basis of the existing models in the literature whereas the last is not very commonly defined but is integrated in this paper as a combination of the main terms. All of these definitions as well as their dimensions and associated models are crucial to study the issue of this thesis. The methods used for the empirical research on this thesis were interpretivism with a deductive approach since the author made use of qualitative collection methods such as semi-structured interviews and secondary data through a case study strategy. All of this methodology was applied due to the subjectiveness of the issue which was more easily met with qualitative data and analysis. As for the main findings in this thesis, they were the synergy between luxury and sustainability; the constancy of sustainable branding in the whole process of luxury business development; and the drivers, enablers, challenges, and barriers affecting the sustainable branding process in luxury hospitality companies. To conclude, the author was able to answer the research question through a revised model of the literature that encompassed all the empirical findings even though there were limitations such as sample size and diversity and some possible language barriers.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business